Troubadours & Troublemakers: Stirring the Network in Transmission & Anti-Transmission - Jeff T. Johnson (Humanities, 2017)
With reference to concepts developed in Trouble Songs: A Musicological Poetics, our objective is to locate trouble (and “trouble”) in and around song, while attending to media forms, transmission processes, and embodied figures that carry trouble through song. These figures include trouble singer, troubadour and DJ, where the latter combines the roles of media curator, Mixmaster and MC. An exploration of and through these interrelated figures serves to elaborate a theory of transmission and anti-transmission of trouble. In all cases we are concerned with the technology of trouble, as well as modes and techniques for its transmission.